2017
DOI: 10.1002/jcb.26104
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Migration Ability Is Modulated by Extracellular Purines in Ovarian Carcinoma SKOV‐3 Cells

Abstract: Extracellular nucleotides and nucleosides have emerged as important elements regulating tissue homeostasis. Acting through specific receptors, have the ability to control gene expression patterns to direct cellular fate. We observed that SKOV-3 cells express the ectonucleotidases: ectonucleotide pyrophosphatase 1 (ENPP1), ecto-5'-nucleotidase (NT5E), and liver alkaline phosphatase (ALPL). Strikingly, in pulse and chase experiments supplemented with ATP, SKOV-3 cells exhibited low catabolic efficiency in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…ENPP1, FH, CYP2E1, HPGDS, ADCY9, NDUFA5, ADH1B and PYGB it characterized in this network. Given the potential molecular mechanisms of the eight MRG, reports on the functions and mechanisms of HPGDS, ADCY9 and NDUFA5 have not been published on OSC [13][14][15][16][17]. However, five of these eight hub MRGs have been studied, namely, ENPP1, FH, CYP2E1, ADH1B and PYGB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ENPP1, FH, CYP2E1, HPGDS, ADCY9, NDUFA5, ADH1B and PYGB it characterized in this network. Given the potential molecular mechanisms of the eight MRG, reports on the functions and mechanisms of HPGDS, ADCY9 and NDUFA5 have not been published on OSC [13][14][15][16][17]. However, five of these eight hub MRGs have been studied, namely, ENPP1, FH, CYP2E1, ADH1B and PYGB.…”
Section: Discussionmentioning
confidence: 99%
“…However, five of these eight hub MRGs have been studied, namely, ENPP1, FH, CYP2E1, ADH1B and PYGB. ENPP1 is increased in ovarian cancer and may promote the migration ability [13]. High level of FH could promote the aggressive and metastatic behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Microarrays were performed in the Microarray Unit at the Institute of Cellular Physiology (UNAM, CDMX, Mexico). Primary cultures of hepatocytes from control and CCl 4 -treated animals were incubated for 24 h with medium or 100 µM UTP [46]. Briefly, RNA was purified through the Trizol method following the manufacturer's instructions (Thermo Fisher Scientific, Waltham, MA, USA).…”
Section: Cdna Microarray Analysismentioning
confidence: 99%
“…Interestingly, these ligands exert complementary or antagonistic actions on each other [9]. For example, epithelial-mesenchymal transition (EMT), a cellular plasticity process important in phenotypic programming of metastatic tumors, can be upregulated by ATP in SKOV-3 cells (from ovarian carcinoma) but downregulated by ADO [10]. This circumstance indicates that enzymes (ectonucleotidases) allowing the sequential conversion from ATP to ADO are a potential regulatory node that controls diverse cellular and physiological responses.…”
Section: Purinergic Communicationmentioning
confidence: 99%
“…Even though extracellular ADO has not been measured in tumors in vivo, there is evidence that ADO levels increase in tumor microdialysates and are more abundant at the core of the tumor [79]. In vitro studies have also indicated that OCDC-derived cell lines release ATP to the cell medium [10,89].…”
Section: Purinergic Signaling In Ovarian Cancermentioning
confidence: 99%